Fermentation of duck bone meal using Bacillus sp., Saccharomyces sp., and Rhizopus sp. for sustainable shrimp (Litopenaeus vannamei) feed (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Surianti, Zainuddin, Aslamyah S, Azis HY. 2025. Fermentation of duck bone meal using Bacillus sp., Saccharomyces sp., and Rhizopus sp. for sustainable shrimp (Litopenaeus vannamei) feed. Biodiversitas 26: 4333-4345. Sustainable aquaculture necessitates alternatives to fishmeal because of its elevated cost and environmental impact. Duck bone waste, an underutilized by-product of poultry processing, can be valorized into feed ingredients, reducing organic waste and supporting a circular bioeconomy. This is the first study to assess Fermented Duck Bone Meal (FDBM) using mixed microbes (Bacillus sp., Saccharomyces sp., and Rhizopus sp.) as a fishmeal substitute in vannamei shrimp diets. Duck bone meal was fermented at inoculum doses of 0.5, 1, and 1.5 mL/100 g and fermentation durations of 12, 24, and 36 h. A control diet contained 100% fishmeal, while four experimental diets substituted fishmeal with optimally fermented duck bone meal (1.5 mL inoculum, 36 hours) at inclusion rates of 25%, 50%, 75%, and 100%, were fed to juvenile shrimp (0.19±0.01 g) for 60 days. Growth, survival, proximate composition, and amino acid profiles were analyzed. Proximate analysis of optimally fermented FDBM (1.5 mL, 36 h) revealed increased crude protein (42.72%), reduced crude fiber (1.49%), and elevated crude lipid (23.46%). Essential amino acids, such as lysine (2.77%) and glutamate (3.54%), were enhanced in the feed, aligning with higher amino acid retention in shrimp muscle (lysine: 4.85%, leucine: 4.57%). Shrimp fed the 75% FDBM diet (Feed D) had the highest final weight (23.04±0.09 g) and biomass weight gain (20.63±0.47 g), compared to the control diet (19.74±1.03 g) and the 25% FDBM diet (19.61±0.53 g), which exhibited the lowest values. Survival rates showed no significant differences among treatments (p>0.05). The 75% substitution of fishmeal with fermented duck bone meal improves prawn growth and feed quality, while reducing reliance on fishmeal, offering a cost-effective and environmentally responsible strategy for sustainable shrimp aquaculture.
Keywords: Amino acid, duck bone meal, Litopenaeus vannamei, proximate, shrimp feed